2011
DOI: 10.1016/j.ejso.2011.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Lymph node examination among patients with gastric cancer: Variation between departments of pathology and prognostic impact of lymph node ratio

Abstract: . Lymph node examination among patients with gastric cancer: variation between departments of pathology and prognostic impact of lymph node ratio. EJSO -European Journal of Surgical Oncology, WB Saunders, 2011, 37 (6) This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 30 publications
1
16
0
1
Order By: Relevance
“…Furthermore, various factors such as different surgical techniques and pathological assessments have made standardized lymph node staging difficult. To overcome these problems, some investigators have proposed the metastatic lymph node rate (Katai et al, 2004;Marchet et al, 2007;Xu, 2010;Lemmens et al, 2011). In line with previous studies, it was showed that higher rate of lymph node metastasis was related to poor prognosis.…”
Section: Discussionmentioning
confidence: 70%
“…Furthermore, various factors such as different surgical techniques and pathological assessments have made standardized lymph node staging difficult. To overcome these problems, some investigators have proposed the metastatic lymph node rate (Katai et al, 2004;Marchet et al, 2007;Xu, 2010;Lemmens et al, 2011). In line with previous studies, it was showed that higher rate of lymph node metastasis was related to poor prognosis.…”
Section: Discussionmentioning
confidence: 70%
“…Other studies demonstrated that the prognosis of the patients was associated with the absolute number of positive lymph nodes when the lymph node sampling was sufficient (16 required by TNM, AJCC 7th edition); however, the metastatic lymph node ratio and log odds of positive lymph nodes may be used to better assess prognosis when lymph node sampling was inadequate (31,32). In addition to the status of lymph node metastasis, the factors affecting the prognosis of gastric cancer also included TNM stage, depth of tumor infiltration, vascular invasion and nerve invasion (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…2,6,8,9,[14][15][16][17][18][19][20][21] Few authors have specifically evaluated the value of LNR in patients with less than 15 nodes included in the surgical specimen. 12,13,22 Sun et al examined 2,159 patients to detect how the number of retrieved lymph nodes influences survival both in pN and LNR staging system. They found that compared with patients with more than 30 retrieved nodes, OS was significantly decreased for pN1 patients with less than 15 nodes, pN2 with less than 20 nodes, and pN3 with less than 25 nodes.…”
Section: Commentsmentioning
confidence: 99%